Предмет: Математика,
автор: Nadfff
Помогите упростить выражения:
y+7*(y-3,1)
1,1x+1,3*(2x-4)
Ответы
Автор ответа:
0
у+21.7у первое уравнение
1.1х-2.6 второе уравнение
1.1х-2.6 второе уравнение
Автор ответа:
6
y+7*(y-3,1)=у+7у-21,7=8у-21,7
1,1x+1,3*(2x-4)=1,1х+2,6х-5,2=3,7х-5,2
1,1x+1,3*(2x-4)=1,1х+2,6х-5,2=3,7х-5,2
Похожие вопросы
Предмет: Русский язык,
автор: Elena934
Предмет: Қазақ тiлi,
автор: dinoshka1
Предмет: Русский язык,
автор: VladislavAkinshin
Предмет: Математика,
автор: zayka6666
Предмет: Геометрия,
автор: kristina6343